Shaping Algeria’s Emi Future: Advancing Beyond Linguistic Competence To Achieve Pedagogical Transformation - Radia , Bouguebs (The Journal of Studies in Language, Culture, and Society, 2025)
The increasing adoption of English as a Medium of Instruction (EMI) in Algerian universities has drawn considerable attention to the challenges and opportunities associated with its implementation. This three-year longitudinal study examines the landscape of EMI integration at Constantine 3 University, focusing on two pivotal phases. The baseline study, conducted in 2023 with twenty-eight (28) faculty members, revealed major concerns related to instructors’ language proficiency and the preservation of academic standards during the early stages of EMI adoption. Building upon these initial findings, the current phase (2025) adopts a mixed-methods approach, combining in-depth interviews with twenty (20) faculty members and institutional document analysis, to examine the role of systemic support structures in addressing persistent barriers. The study focuses specifically on disparities between STEM (Science, Technology, Engineering, and Mathematics) and humanities disciplines and the emerging role of English for Specific Purposes (ESP) practitioners in bridging these gaps. The study findings reveal three enduring institutional deficiencies: uneven professional development pathways, the absence of standardized frameworks for material adaptation, and limited collaboration between subject-matter faculty and ESP specialists. Importantly, the data demonstrate that strategic ESP integration, through initiatives such as co-teaching and discipline-specific language scaffolding, can effectively mitigate 65% of the pedagogical challenges identified in 2023. The study concludes by proposing a tripartite framework for EMI enhancement: (a) university-level EMI resource centers to offer centralized guidance and training; (b) discipline-specific teaching partnerships to cultivate collaborative expertise; and (c) diagnostic tools to assess student preparedness and promote equitable access to EMI programs. These empirically grounded recommendations align with Algeria’s 2030 academic internationalization agenda and provide practical insights into EMI advancement within multilingual higher education contexts in the Global South.